2016
DOI: 10.1097/tp.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Outcomes of Posttransplant Smoking in Solid Organ Transplant Recipients

Abstract: Posttransplant smoking is associated with poor outcomes. Our results might help clinicians to understand which patients are more likely to smoke posttransplant, guide interventional approaches, and provide recommendations for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 53 publications
1
48
0
1
Order By: Relevance
“…While in line with previously reported numbers, this prevalence is presumably underestimated, bearing in mind that we used self‐report to document smoking . Given that post‐transplant smoking significantly reduces graft and patient survival, we recommend that HTx programs regularly assess patients’ smoking status via more objective means, for example, exhaled CO measurement, and should implement effective smoking cessation programs …”
Section: Discussionsupporting
confidence: 53%
“…While in line with previously reported numbers, this prevalence is presumably underestimated, bearing in mind that we used self‐report to document smoking . Given that post‐transplant smoking significantly reduces graft and patient survival, we recommend that HTx programs regularly assess patients’ smoking status via more objective means, for example, exhaled CO measurement, and should implement effective smoking cessation programs …”
Section: Discussionsupporting
confidence: 53%
“…Duerinckx et al conducted a meta-analysis to investigate the correlates and outcomes associated with post-transplant smoking after solid organ transplantation[14]. They found that post-transplant smoking was associated with higher odds of newly developed cardiovascular disease, de novo malignancies, and a shorter survival time after liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Lifelong medication intake and monitoring of graft function is needed, and onset of comorbidities, such as hypertension, diabetes, cancer, or hyperlipidemia, for instance, will contribute to the burden of chronic illness management. Moreover, as has also been demonstrated in the MALT study and by others, medication nonadherence elevates the risk of late acute rejection, and increasing evidence likewise shows that other behavioral (eg, smoking) and psychosocial (eg, depression) factors negatively impact graft and patient survival . The goal of chronic illness management is therefore to ensure continuity and coordination of care and to make sure adherence, lifestyle, and psychosocial support is structurally embedded in the longterm follow‐up.…”
mentioning
confidence: 73%